Anglican Approaches to Christian–Muslim Dialogue - Ipgrave, Michael (Journal of Anglican studies, 2005)
Three aspects of the Anglican understanding of Christianity can make a distinctive contribution to Christian–Muslim dialogue today. Recognition of the importance of context highlights the complexity and variety of the situations in which Christians and Muslims encounter one another. Basing unity on a sense of collegiality which can withstand disagreement offers a model for shared working across religious differences. The interpretation of Scripture through reason and tradition under the guidance of conscience points to a dialogue between those addressed by the Bible and by the Qur'ān respectively. These themes are illustrated through contemporary Anglican involvement in three Christian–Muslim projects, and their theological implications are explored.